2020
DOI: 10.1038/s41435-019-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic variants associated with circulating levels of sgp130. Results from the IMPROVE study

Abstract: The genes regulating circulating levels of soluble gp130 (sgp130), the antagonist of the inflammatory response in atherosclerosis driven by interleukin 6, are largely unknown. Aims of the present study were to identify genetic loci associated with circulating sgp130 and to explore the potential association between variants associated with sgp130 and markers of subclinical atherosclerosis. The study is based on IMPROVE (n = 3703), a cardiovascular multicentre study designed to investigate the determinants of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
(55 reference statements)
0
11
1
Order By: Relevance
“…There are three sgp130 isoforms [ 95 ]: sgp130-RAPS [ 96 ], sgp130-E10 [ 97 ], and full-length sgp130 [ 98 ]. Unfortunately, there is no information on the secretion of these isoforms during exercise.…”
Section: Hyper-il-6 and Sgp130 Production During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…There are three sgp130 isoforms [ 95 ]: sgp130-RAPS [ 96 ], sgp130-E10 [ 97 ], and full-length sgp130 [ 98 ]. Unfortunately, there is no information on the secretion of these isoforms during exercise.…”
Section: Hyper-il-6 and Sgp130 Production During Exercisementioning
confidence: 99%
“…Unfortunately, there is no information on the secretion of these isoforms during exercise. Additionally, the genes that regulate sgp130 levels are largely unknown [ 95 ].…”
Section: Hyper-il-6 and Sgp130 Production During Exercisementioning
confidence: 99%
“…The factors inducing sgp130 production through alternative splicing are unknown. We have recently shown that about genetic variants contribute to determine sgp130 circulating levels in serum and explain 11% of the variance (93).…”
Section: The Soluble Glycoprotein 130mentioning
confidence: 99%
“…The sgp130-E10 isoform on the other hand accounts merely for 1-2% of circulating sgp130 (95). The isoform most efficient in inhibiting IL6 trans-signalling is the full length sgp130 with inhibition executed in an autocrine fashion in cells secreting protective sgp130 (92,93). In addition, in an in vitro experimental setting, it was demon strated that monocytes expressed the full-length sgp130 albeit the expression disappeared upon their differentiation into macrophages (92).…”
Section: The Soluble Glycoprotein 130mentioning
confidence: 99%
“…A missense variant (Gly148Arg) in exon 5 of the IL6ST gene, rs2228044, that has been associated with higher serum sgp130 levels ( 59 ) is not in LD with rs7731626 ( R 2 = 0.0008 in the European population), ruling out a mechanistic correlation. In light of these current observations, and considering serum sgp130 appears to be a polygenic trait influenced by genomic variants acting in trans ( 60 ), decreased circulating sgp130 levels constitute likely a secondary effect of the major causative link to MS risk conferred by rs7731626, which thus far is understood as upregulation of both ANKRD55 and IL6ST expression in CD4 + T lymphocytes ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 92%